Post chemotherapy febrile neutropenia. Length of stay and experience in our population - Íñigo Pérez-Heras; Roberto Carlos Raynero-Mellado; Raquel Díaz-Merchán; Nerea Domínguez-Pinilla (Elsevier, 2020)
Introduction: Infections are a significant cause of morbidity and mortality in cancer patients (mortality is estimated at around 3%). Febrile neutropenia often leads to the hospitalisation of cancer patients, increasing the risk of nosocomial infection, as well as health costs due to the hospital admission. Methods: An ambispective (01 July 2015-12 July 2018) observational study was conducted on all episodes of chemotherapy-induced febrile neutropenia in a paediatric population. A record was made of age, gender, weight percentile (WHO), length of hospital stay (days), temperature (°C), microbial isolation, infectious source, antibiotic or antifungal prophylaxis, haemoglobin (g/dl), platelets (/mm3), neutrophils (/mm3), lymphocytes (/mm3), monocytes (/mm3), CRP (mg/L) and procalcitonin (PCT) (ng/ml) on admission, and days with neutropenia < 500/mm3. Statistical analysis was performed using the SPSSv.23 program. Results: The study included 69 patients, and 101 episodes were recorded. The mean stay was 7.43 days (median 6 days). Microbial isolation was found in 44.6% of the episodes, with no infectious source identified in 36% of them. An inverse correlation was found between haemoglobin, platelets, and lymphocytes on admission and the hospital stay (−0.356: P = .001, −0.216: P = .042, and −0.216: P = .042, respectively). The mean stay was greater if there was a CRP >90 mg/L (10.94 vs. 6.66 days, P = .017), if PCT > 1 ng/ml (16.50 vs. 6.77 days, P = .0002), if ≤100 neutrophils (8.27 vs. 5.04 days P = .039) on admission, and if there was microbe isolation (9.54 vs. 5.78 days P = .006) Conclusion: The relationship between haemoglobin, platelets, and lymphocytes on admission and the mean stay is inversely proportional. In addition, those patients with ≤100 neutrophils, CRP > 90 mg/L, and PCT > 1 ng/ml on admission had a longer hospital stay. Resumen: Introducción: Las infecciones son una causa importante de morbimortalidad en los pacientes con cáncer (mortalidad estimada en 3%). La neutropenia febril conlleva con frecuencia el ingreso hospitalario de los pacientes oncológicos, incrementando el riesgo de infección nosocomial así como los costes sanitarios por ingresos. Métodos: Estudio observacional ambispectivo (01/07/2015-31/12/2018) de los episodios de neutropenia febril post-quimioterapia en población pediátrica. Se recogieron edad, sexo, percentil de peso(OMS), estancia hospitalaria(días), temperature (°C), aislamiento de germen, foco infeccioso, profilaxis o no antibiótica y antifúngica, cifras de hemoglobina(g/dl), plaquetas(/mm3), neutrófilos(/mm3), linfocitos(/mm3), monocitos(/mm3), proteína C reactiva (PCR)(mg/L) y procalcitonina(PCT)(ng/ml) al ingreso y días con neutropenia <500/mm3. El análisis estadístico se realizó con el programa SPSSv.23. Resultados: De 69 pacientes, se registraron 101 episodios. La estancia media fue de 7,43 días (mediana 6 días). Se aisló germen en un 44.6% de los episodios, no identificándose foco infeccioso en un 36% de los mismos. Se halló correlación inversa entre hemoglobina, plaquetas y linfocitos al ingreso con la estancia hospitalaria (−0,356 (p0,001); −0,216 (p0,042) y −0,216(p0,042) respectivamente). La estancia media fue mayor si al ingreso presentaron PCR > 90 mg/L(10,94 vs.6,66 días p0,017), si PCT > 1 ng/ml (16,50 vs.6,77 días p0,0002), si ≤100neutrófilos(8,27vs.5,04 días p0,039) y si hubo aislamiento microbiológico (9,54vs.5,78 días p0,006). Conclusión: La relación entre hemoglobina, plaquetas y linfocitos al ingreso con la estancia media es inversamente proporcional. Además, aquellos pacientes con ≤100 neutrófilos al ingreso, PCR>90 mg/L y PCT>1 ng/ml presentaron mayor estancia media. Estos factores podrían ser importantes en el manejo de la neutropenia febril en el paciente con cáncer infantil.